Influence of magnetic field strength on nanoparticle growth in a capacitively-coupled radio-frequency Ar/C2H2 discharge. (12th February 2019) - Couëdel, L; Artis, D; Khanal, M P; Pardanaud, C; Coussan, S; LeBlanc, S; Hall, T; Jr, E Thomas; Konopka, U; Park, M; Arnas, C
Abstract: The growth of nanoparticles in a magnetised chemically active discharge (Ar/C2 H2 ) is investigated. The influence of the strength of the magnetic field on dust particle growth dynamics is explored. The structure of the grown nanoparticles is studied ex situ . It is revealed that the strength of the magnetic field (up to 2.5 T) has a major impact on discharge parameters (such as the self-bias of the powered electrode) as well as on the growth and morphology of the nanoparticles. At high magnetic field, the dust cloud is confined in the sheath above the grounded electrode while without magnetic field the dust cloud occupies most of the interelectrode space. Moreover, at high magnetic field, large porous spherical agglomerates were grown. The modification of the self-bias is explained by the influence of the magnetic field on the diffusion of charged species resulting in a confinement of the plasma under the powered electrode. Complementary particle-in-cell simulations confirm that the electric field and plasma distributions are strongly affected by the magnetic field explaining the experimentally observed dust cloud localisation. The large porous spherical agglomerates are most probably due to an enhanced agglomeration caused by the modified confinement owing to the magnetic field.